مكانة اللغة العربية في سياق الثقافة المحلية بمادورا - Rousul Firdaus; Husnul Khotimah (Yayasan Mutiara Hati Moeslem, 2026)
This study aims to explore the relationship between the Arabic language and the local culture of the Madurese community in the context of the rokat tradition in Pao Taber Hamlet, Jelbudan Village, Dasuk District, Sumenep Regency. Rokat is a traditional ritual that serves as a means of seeking safety, protection, and well-being. Alongside the development of Islamic teachings, this tradition has undergone a process of Islamization through the integration of religious elements such as the recitation of prayers, verses from the Qur'an, and shalawat, all delivered in Arabic. This research adopts a qualitative approach with a phenomenological method, collecting data through in-depth interviews with five informants and literature review. The findings demonstrate that Arabic in the rokat ritual functions not merely as a liturgical language but as a symbolic marker of Islamic religiosity, sacred authority, and collective identity. More importantly, this study reveals that Arabic operates as a mechanism of cultural negotiation, mediating the integration of Islamic values with residual Hindu-Buddhist elements embedded in local tradition. Unlike previous studies that tend to describe the rokat ritual from a general anthropological or cultural perspective, this research highlights the central role of language as a strategic instrument in constructing and legitimizing the socio-religious identity of the Jelbudan community. Thus, the rokat tradition represents not only a form of cultural continuity but also a dynamic process of identity formation shaped through linguistic symbolism.